Cotton.Go’s Electronic Service Quality Improvement Using Importance Performance Competitor Analysis Approach - Tara Aldiera; Sari Wulandari; Ima Normalia Kusmayanti (School of Industrial and System Engineering, Telkom University, 2021)
The number of competitors that have sprung up in the field of fashion especially in men's clothing, has caused Cotton.Go need to evaluate its e-commerce services to compete with them. Therefore, this research was conducted to evaluate the attributes of Cotton.Go’s e-commerce services by integrating the dimensions of Electronic Service Quality and Importance Performance Competitor Analysis (IPCA) method. According to research result, seven attributes of services in Cotton.Go’s e-commerce is needed for further research, which are web design, reliability, efficiency, responsiveness, security, flexibility, and fulfillment. This research produced that all of the attributes need urgent action to improve by looking at the negative performance differences value with its competitor. All attributes that need to be improved indicated that the performances are considered to be lower compared to the competitor and need immediate action to improve.